2020
DOI: 10.3390/su12187315
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Heavy Metals on Soil Collected from Lixisol of Typical Karst Areas in the Presence of CaCO3 and Soil Clay and Their Competition Behavior

Abstract: The content of heavy metals in the soil in Guizhou Province, which is a high-risk area for heavy metal exposure, is significantly higher than that in other areas in China. Therefore, the objective of this study was to evaluate the ability of CaCO3 and clay to accumulate heavy metals in topsoil sample collected from Lixisol using the method of indoor simulation. The results showed that the contents of Cu, Zn, Cd, Cr, Pb, Hg and As in the soil sample were 10.8 mg/kg, 125 mg/kg, 0.489 mg/kg, 23.5 mg/kg, 22.7 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Some studies also claim that Cr and Cd in the residual fraction of rice rhizosphere soil shows negative correlations with catalase activity. However, soil heavy metal activities are different with different planting patterns, especially under high background conditions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also claim that Cr and Cd in the residual fraction of rice rhizosphere soil shows negative correlations with catalase activity. However, soil heavy metal activities are different with different planting patterns, especially under high background conditions [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Several chemical mechanisms have been intensively investigated to immobilize heavy metals in soils involving adsorption and precipitation [12][13][14][15][16][17][18][19]. ese mechanisms have been reported to lower the heavy metal labile fractions in the soils [20][21][22]. Previous researches showed that the increase in soil pH by liming and in soil colloid negative charges by organic matter amendment significantly reduced the DTPA-extracted Cu, Cd, and Zn in some tropical soils including Ultisols, Oxisols, and Alfisols.…”
Section: Introductionmentioning
confidence: 99%
“…e negative effects of industrial waste-borne Cu and Zn on the growth of spinach (Amaranthus spinosus L.) and corn (Zea mays L.) were attenuated by lime and/or cassava-leaf compost amendment [23]. Some other soil workers also reported the reducing effects of lime and/or organic matters on soil heavy metal concentrations [22,[24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and an alkaline zeolite, and optionally also another sorbent of abiotic origin (e.g., CaCO 3 ). Each of these components has shown a positive effect on reducing the content of some PTEs, e.g., perlite: Pb, Cu, Ni, Cd, [38]; chicken manure: Cd, Ni [39,40]; CaCO 3 : Pb, Cu, Cd [41,42]. Zeolites have a positive effect on the fertility and sorption properties of the soil and the formation of phytomass [43,44].…”
Section: Introductionmentioning
confidence: 99%